Laboratory Investigation on Improving Strength of Weak Subgrade Soil using Saw Dust Ash with Stone Dust - Dhimal, Suman; Gautam, Gopal (Journal of Science and Technology, 2024)
Performance of Flexible Pavement depends on the functions of the component layers especially subgrade. Subgrade is natural layer of soil which takes all load of pavement as well as load coming to pavement. Stability of pavement depends upon stability of subgrade. The conventional approach of stabilization of soft subgrade is to remove the soft soil, and replace it with soil of high strength. The high cost of replacement of weak soil has caused highway agencies to assess alternative methods to construct the highway over weak subgrade. Soil stabilization is one of the most suitable alternatives which are widely used in pavement construction. Soil stabilization can be achieved by treating it with various admixtures. Different solid wastes such as rice husk ash, saw dust ash and fly ash can be used to stabilize soils in place of (or in addition to) cement or lime. In this research Saw Dust Ash (SDA) and Stone Dust (SD) has been selected as a stabilizer. The California bearing ratio (CBR) and unconfined compression strength (UCS) test is conducted by making the specimens of weak sub-grade by adding the variable percentages of mixture of SDA and stone dust. First the soil is mixed up with SDA up to 8% by weight with an increment of 2%. Then an optimum value at 4% of SDA was determined on the basis of some geotechnical properties of mixture and weak sub-grade soil. Again, the test soil samples were prepared by mixing with varying proportion of stone dust from 10% to 30% at 4% optimum value of SDA constantly. The CBR, UCS and maximum dry density values were determined of modified soil. The soaked CBR and UCS value of weak subgrade soil increased 2.1 and 2.16 times respectively after modified by 20% stone dust with constant 4% SDA and total pavement thickness decreased to 775 mm. The minimum pavement construction cost per square meter with combination of 4% SDA and 20% SD which is economical by 1.73% than conventional method. Hence, strengthening by SDA and SD is found economical.